2021
DOI: 10.1093/ehjci/jeab076
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical relevance of left atrial appendage membranes: a new congenital heart disease?

Abstract: Aims Left atrial appendage (LAA) membranes are rare congenital anomalies. Those involving the appendage orifice may obstruct its emptying flows, thus promoting blood stasis and clot formation. However, the epidemiology of LAA membranes has never been studied and a correlation with appendage thrombosis has never been proved. Very few case reports described LAA membranes, therefore, their frequency and clinical significance are not known. Moreover, their presence and degree are of crucial impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The prevalence of LAAOS is not well established, but a retrospective review of adults with atrial fibrillation found a prevalence of LAA membranes of 1 per 1000, only half of which caused obstruction. 3 While reported as a congenital anomaly, the authors did not have long term serial imaging to support this claim in a population of adults.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The prevalence of LAAOS is not well established, but a retrospective review of adults with atrial fibrillation found a prevalence of LAA membranes of 1 per 1000, only half of which caused obstruction. 3 While reported as a congenital anomaly, the authors did not have long term serial imaging to support this claim in a population of adults.…”
Section: Discussionmentioning
confidence: 93%
“…The clinical significance of LAAOS is not clear. Due to the known risk of thrombus formation in the LAA, LAAOS has been proposed to further increase this risk secondary to compromised flow and potential stasis caused by the membrane 3,4,6 . Interestingly, some have argued that even if there is thrombus formation within the LAA, the smaller orifice due to LAAOS could be protective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, using 3D image, they confirmed the narrowed LAA orifice. Cresti et al 2 demonstrated that the prevalence of LAA membranes was 1 of 1000 in their study. Those involving the appendage orifice may obstruct its emptying flows, thus promoting blood stasis and clot formation.…”
mentioning
confidence: 75%